Pemberian tehnik distraksi menonton kartun animasi untuk menurunkan tingkat nyeri prosedur invasif pada anak - Riska Wandini; Riyan Resandi (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
Effectiveness of cartoon distraction on pain perception with children having invasive proceduresBackground: Number of children had hospitalized at Dr. A. Dadi Tjokrodipo hospital of Bandar Lampung every year around of 840-900 children, and most of them are having general invasive procedures such as taking blood samples and intravenous infusionPurpose: Knowing effectiveness of cartoon distraction on pain perception in children during taking blood samples.Method: This type of research is quantitative. The research design of the Quasi-Experimental method post only approaches with group control. The sample of 16 children. Data analysis uses univariate and bivariate with t-test.Results: Characteristics of respondents based on age at most are 4-5 years of age as many as 5 respondents (31.3%) and most genders are male as many as 11 respondents (68.8%). The average pain in taking blood in a child before distraction watching a cartoon video with 16 children, with a mean of 7.81 standard deviations of 1.047, after being given intervention with a mean of 3.38 standard deviations of 1,821. The results of statistical tests using the dependent test obtained 2 mean difference values before and after being given distraction therapy watching cartoon videos was 4.43 with a p-value of 0,000 (α <0.05).Conclusion: There was effectiveness of cartoon distraction on pain perception in children during taking blood samples. Suggestions can provide information for the development of nursing about distraction techniques watching animated videos in children who experience pain, to reduce the incidence of stress due to hospitalization in children.Keywords: Cartoon distraction; Pain perception; Taking blood samples; childrenPendahuluan: Jumlah anak yang dirawat di RSUD Dr. A. Dadi Tjokrodipo Kota Bandar Lampung setiap tahunnya sekitar 840-900 anak, dengan perlakukan pengambilan darah pada anak sebanyak 20 anak per bulan, sedangkan pemasangan infus sebanyak 420 anak pertahun, dengan rata-rata per bulan 35 anak. Tujuan: Diketahui pengaruh terapi distraksi menonton video kartun dengan pengurangan nyeri pada pengambilan darah pada anak.Metode: Jenis penelitian adalah Kuantitatif. Desain penelitian metode Quasi Eksperimental pendekatan one group pretest-posttest design. Sampel sebanyak 16 anak orang. Analisa data mengguanakan univariat dan bivariate dengan t-tes.Hasil: Karakteristik responden berdasarkan Usia paling banyak adalah usia 4-5 tahun sebanyak 5 responden (31,3%) dan jenis kelamin terbanyak adalah laki-laki sebanyak 11 responden (68,8%). Rata-rata nyeri pengambilan darah pada anak sebelum dilakukan distraksi menonton video kartun terhadap 16 orang anak, dengan mean 7,81 standar deviasi 1,047, setelah diberikan intervensi dengan mean 3,38 standar deviasi 1,821. Hasil uji statistik menggunakan test-dependen didapat nilai beda 2 mean sebelum dan sesudah diberikan terapi distraksi menonton video kartun adalah 4,43 dengan p-value 0.000 (α<0.05).Simpulan: Terdapat pengaruh terapi distraksi menonton video kartun dengan pengurangan nyeri pada pengambilan darah pada anak. Saran Dapat memberi informasi bagi perkembangan keperawatan tentang teknik distraksi menonton video animasi pada anak yang mengalami nyeri, hingga dapat mengurangi kejadian stress akibat hospitalisasi pada anak.